Integration of Occupational Safety and Health Awareness and Compliance in the Implementation of Land Surveying Practices in Vocational High Schools - Fuad, Muhammad Nur; Kusumawardani, Rini; Supraptono, Eko; Sutopo, Yeri; Handayani, Sri (Universitas Negeri Semarang, 2024)
Occupational Safety and Health (OSH) is a crucial aspect of land surveying practices conducted by vocational high school students. The risk of accidents, such as falls, being buried by soil, and exposure to extreme weather conditions, necessitates the optimal implementation of OSH awareness and compliance. This study aims to analyze the integration of student awareness and compliance with OSH in land surveying practices. The research employs a quantitative approach using multiple linear regression analysis. Prior to analysis, the data were tested for (1) normality, (2) homogeneity, and (3) linearity. The study population consists of 105 students from the Construction and Housing Engineering program at SMK Negeri 3 Semarang, selected through a total sampling technique. Data were collected through questionnaires, observations, and interviews, then analyzed using SPSS. The results indicate that student awareness and compliance significantly and simultaneously influence OSH implementation, contributing 78%. The correlation analysis reveals a strong relationship of 88% between the variables. Students with high awareness and compliance demonstrate greater discipline in adhering to OSH procedures in the field. These findings suggest that enhancing education, providing adequate safety facilities, and enforcing strict supervision can further improve OSH implementation in land surveying practices within vocational school environments.